2010
DOI: 10.1016/j.ecss.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate variability on an east Australian bay

Abstract: The climate along the subtropical east coast of Australia is changing significantly. Rainfall has decreased by about 50 mm per decade and temperature increased by about 0.1 C per decade during the last fifty years. These changes are likely to impact upon episodes of hypersalinity and the persistence of inverse circulations, which are often characteristic features of the coastal zone in the subtropics and are controlled by the balance between evaporation, precipitation, and freshwater discharge. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Previous analysis of three extreme river discharge events in the Hervey Bay region found that the freshwater plume-impacted coastal zone of the inner-shelf extends only a few kilometres from the coast (Gräwe et al, 2010). Water depth is well below the 40 m threshold previously introduced.…”
Section: Mao and Luick 2014) The Study Site Was Previously Identifiementioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis of three extreme river discharge events in the Hervey Bay region found that the freshwater plume-impacted coastal zone of the inner-shelf extends only a few kilometres from the coast (Gräwe et al, 2010). Water depth is well below the 40 m threshold previously introduced.…”
Section: Mao and Luick 2014) The Study Site Was Previously Identifiementioning
confidence: 99%
“…It was hypothesised that strong bottom Ekman layer flux resulted in the observed uplift of nutrient-rich (phosphate, nitrate and silicate) water onto the shelf. Gräwe et al (2010) found evidence of a sporadic upwelling event just to the north of Sandy Cape at 24.5 o S in hydrography data from a Hervey Bay survey during December 2007. Rossi et al (2014) focused their analysis of eastern coastal upwelling on a region south of 28 o S using 10 years of remotely sensed wind data.…”
Section: Description Of the Study Sitementioning
confidence: 99%
“…El cambio climático es generalmente asociado al incremento de la temperatura, ya que éste es un parámetro básico medible; éste también causa cambios en los patrones del viento [9] [10], en la intensidad o frecuencia de tormentas [11] [12]; así como también de la lluvia y de la escorrentía [5] [13]. Aunque no se ha llegado a un consenso sobre la actividad futura de la actividad de El Niño [14] [15], recientemente encontraron, después de hacer 79 simulaciones de doce diferentes modelos climáticos, acoplando el océano y la atmósfera, y evaluando seis diferentes escenarios del IPCC, un incremento en el número de anomalías del tipo La Niña en el sector del océano Pacífico a partir del 2050.…”
Section: Introductionunclassified
“…Recent studies have also suggested that Hervey Bay (Queensland) has inverse salinity throughout most of the year and that such conditions may persist with drought (Ribbe 2006;Gräwe et al 2010). Inverse salinity in northern Australia is likely only during the dry season and will depend on rainfall changes associated with climate change.…”
Section: Future Scenarios Of Climate Change In Estuariesmentioning
confidence: 99%
“…In northern Australia, altered rainfall and river flows are suggested to be more important factors as a consequence of climate change than are increases in temperature (Hobday et al 2008). Reduced river flows have already occurred in eastern Australia (Gräwe et al 2010). The direct human use of water resources (e.g.…”
Section: Tropical Australian Estuariesmentioning
confidence: 99%